Time-frequency Correlation Function's Application in Pipeline Leakage Localization; Proceedings of the Junior Scientist Conference 2010, Vienna, April 7-9, 2010 - Chau Tran (2010, 2010)
В фонде НТБ ТПУ отсутствует